Broadband ase source using bismuth-based erbium-doped fibers in double-pass set-up - Cheng, X.S.; Ahmad, Harith; Harun, Sulaiman Wadi (John Wiley & Sons, 2010)
Flat and broadband amplified spontaneous emission (ASE) spectrum, which covers both C and L-band regions is demonstrated. The ASE source employs 49 and 215 cm long Bismuth-based erbium-doped fiber (Bi-EDF) to provide C- and L-band amplifications, respectively as gain media in conjunction with double-pass linear configuration. The ASE power level obtained varies from -24 to -35 dBm within 85 nm bandwidth from 1530 to 1615 nm at the optimum pump powers combination. The total ASE power reaches up to 26 mW at maximum total pump power of 320 mW, which can be translated to 8% efficiency. (C) 2010 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 1636-1638, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.25239